Si Griseldis m’était conté : entre attendrissement et enseignement - Loba, Anna (Studia Romanica Posnaniensia, 2018)
My intention is to show in this article the role of emotions in the reception and dissemination of the Griselda story. Petrarch’s affective reactions to Boccaccio’s tale opened the path that many authors would pursue. I propose to trace the transition from the strange and confusing story to didactic and exemplary and explain the place of Griselda in courtesy literature addressed to women in the late Middle Ages.